The Indonesian Coconut Oil Export Opportunities with Main Trade Partner Countries in the International Market - Herdiana Anggrasari; Ayu Kumala Sari; Fadilla Ristya Arminda (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This study examines the opportunities for trade administration of Indonesian coconut oil in major trading partner countries in terms of the development of area size, production and productivity of coconuts, competition in the marketing of coconut oil, and demand for coconut oil in the international market. The purpose of this research is to (1) develop of area, production, and productivity of coconut in Indonesia, (2) analysis of the competitiveness of Indonesian coconut oil in major trading partner countries, and (3) analysis of trend analysis of demand for Indonesian coconut oil in the international market. The data used in this research is secondary data from UN Comtrade for 25 years (1997-2021) and FAO for 61 years (1961-2001). The method used is to describe the development of a land area, production, and production of coconut in Indonesia and the development of demand for coconut oil in Indonesia in the international market. Revealed Comparative Trade Advantage (RCTA), Revealed Symmetric Comparative Advantage (RSCA), and Trade Balance Index (TBI) analysis methods are used to determine the competitiveness of Indonesian coconut oil in the major trading countries. In addition, a product map is created based on changes in the competitiveness of Indonesian coconut oil products among the main trading partners. The results showed an increase in area, production, and production of coconuts annually. Indonesia has intense competition for coconut oil in its major trading countries. In addition, the demand for coconut oil in the international market will continue to increase due to the ever-increasing industrial needs. This is an opportunity to expand the coconut market share internationally.